Enhanced Chondrocyte Proliferation in a Prototyped Culture System with Wave-Induced Agitation - Pilarek Maciej; Godlewska Klaudia; Kuźmińska Aleksandra; Wojasiński Michał; Dąbkowska Katarzyna (Chemical and Process Engineering)
One of the actual challenges in tissue engineering applications is to efficiently produce as high of number of cells as it is only possible, in the shortest time. In static cultures, the production of animal cell biomass in integrated forms (i.e. aggregates, inoculated scaffolds) is limited due to inefficient diffusion of culture medium components observed in such non-mixed culture systems, especially in the case of cell-inoculated fiber-based dense 3D scaffolds, inside which the intensification of mass transfer is particularly important. The applicability of a prototyped, small-scale, continuously wave-induced agitated system for intensification of anchorage-dependent CP5 chondrocytes proliferation outside and inside three-dimensional poly(lactic acid) (PLA) scaffolds has been discussed. Fibrous PLA-based constructs have been inoculated with CP5 cells and then maintained in two independent incubation systems: (i) non-agitated conditions and (ii) culture with wave-induced agitation. Significantly higher values of the volumetric glucose consumption rate have been noted for the system with the wave-induced agitation. The advantage of the presented wave-induced agitation culture system has been confirmed by lower activity of lactate dehydrogenase (LDH) released from the cells in the samples of culture medium harvested from the agitated cultures, in contrast to rather high values of LDH activity measured for static conditions. Results of the proceeded experiments and their analysis clearly exhibited the feasibility of the culture system supported with continuously wave-induced agitation for robust proliferation of the CP5 chondrocytes on PLA-based structures. Aside from the practicability of the prototyped system, we believe that it could also be applied as a standard method offering advantages for all types of the daily routine laboratory-scale animal cell cultures utilizing various fiber-based biomaterials, with the use of only regular laboratory devices.